What does it mean to decolonise the school music curriculum? (UCL Press, 2022)
In many ways the school music curriculum has become increasingly diverse since the 1970s. For example, 'pop' and 'world' musics have been listed in UK curricula and syllabuses with an aim of becoming more inclusive. However, this article argues that such approaches to curriculum as content have confounded social justice in school music, and in particular when perpetuating a prejudicial discourse. To understand this discourse, three 'distortions' of the material nature of musical knowledge are explored as potential sources of ongoing student alienation from school music: reification, hegemonic appropriation and the loss of meaning. These distortions are also exemplified through a case study critique of social realism and the UK government's Model Music Curriculum. By way of conclusion, and as a possible resolution to the distortions, some characteristics of a curriculum as process are proposed that have implications for decolonisation and wider issues of social justice, such as class and gender.